2020
DOI: 10.1002/ejhf.1749
|View full text |Cite
|
Sign up to set email alerts
|

Limited role for fibroblast growth factor 23 in assessing prognosis in heart failure patients: data from the TIME‐CHF trial

Abstract: Aim Fibroblast growth factor 23 (FGF23) is an intensively studied biomarker at the crossroads of cardiovascular disease, heart failure (HF) and chronic kidney disease. Independent associations between increasing FGF23 levels and cardiovascular events were found in many, but not all studies. By analysing data from the TIME‐CHF cohort, we sought to investigate the prognostic value of FGF23 in an elderly, multimorbid HF patient cohort. We determined differences between intact (iFGF23) and C‐terminal FGF23 (cFGF23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 43 publications
1
23
0
2
Order By: Relevance
“…In the TIME CHF study, FGF23 was found to be higher in HFpEF than in HFrEF but was not associated with risk of death or HF hospitalization. 21 Similarly, FGF23 was not associated with mortality risk in patients undergoing coronary angiography in the Ludwigshafen Risk and Cardiovascular (LURIC) Health Study. 22 While our observations of increased risk of adverse outcome in association with elevated FGF23 appear to contrast with those of TIME CHF and LURIC, 21,22 the former included only 73 patients with HFpEF, and neither was a specific study of HFpEF.…”
Section: Discussionmentioning
confidence: 97%
“…In the TIME CHF study, FGF23 was found to be higher in HFpEF than in HFrEF but was not associated with risk of death or HF hospitalization. 21 Similarly, FGF23 was not associated with mortality risk in patients undergoing coronary angiography in the Ludwigshafen Risk and Cardiovascular (LURIC) Health Study. 22 While our observations of increased risk of adverse outcome in association with elevated FGF23 appear to contrast with those of TIME CHF and LURIC, 21,22 the former included only 73 patients with HFpEF, and neither was a specific study of HFpEF.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, as indicators of pathological processes and responses to therapeutic interventions, circulating blood biomarkers have been increasingly studied due to their noninvasive determinations that tend to be su ciently sensitive and accurate. Although there many different available biomarkers (e.g., NT-proBNP [3] , GDF-15 [4] ), there are also multiple factors that affect the prognostic values of these biomarkers.…”
Section: Highlightmentioning
confidence: 99%
“…gerade zur Früherkennung von CKD und deren myokardialen Risikenin die Routine einzuschleusen, hat sich nicht bewahrheitet. Aktuelle Studiendaten zu FGF23 stellen seine Aussagekraft als kardialen Biomarker wieder infrage [13].…”
Section: Biomarkerunclassified